Journey toward a Patient-Centered Medical Home: Readiness for Change in Primary Care Practices - Wise, Christopher G (Blackwell Publishing Inc, 2011)
Context: Information is limited regarding the readiness of primary care practices to make the transformational changes necessary to implement the patient-centered medical home (PCMH) model. Using comparative, qualitative data, we provide practical guidelines for assessing and increasing readiness for PCMH implementation. Methods: We used a comparative case study design to assess primary care practices' readiness for PCMH implementation in sixteen practices from twelve different physician organizations in Michigan. Two major components of organizational readiness, motivation and capability, were assessed. We interviewed eight practice teams with higher PCMH scores and eight with lower PCMH scores, along with the leaders of the physician organizations of these practices, yielding sixty-six semistructured interviews. Findings: The respondents from the higher and lower PCMH scoring practices reported different motivations and capabilities for pursuing PCMH. Their motivations pertained to the perceived value of PCMH, financial incentives, understanding of specific PCMH requirements, and overall commitment to change. Capabilities that were discussed included the time demands of implementation, the difficulty of changing patients' behavior, and the challenges of adopting health information technology. Enhancing the implementation of PCMH within practices included taking an incremental approach, using data, building a team and defining roles of its members, and meeting regularly to discuss the implementation. The respondents valued external organizational support, regardless of its source. Conclusions: The respondents from the higher and lower PCMH scoring practices commented on similar aspects of readiness—motivation and capability—but offered very different views of them. Our findings suggest the importance of understanding practice perceptions of the motivations for PCMH and the capability to undertake change. While this study identified some initial approaches that physician organizations and practices have used to prepare for practice redesign, we need much more information about their effectiveness.